Characterization of service intervals and frequency of short oestrus cycles in Zebu (Bos indicus) cows in Ethiopia - Mukasa-Mugerwa, E.; Tegegne, Azage; Teklu, Y. (1991)
Presents results of a data collected over a 10-year period on 1,778 service intervals in 1,111 Arsi (Bos indicus) cows at the Ethiopian Ministry of Agriculture ranch to analyse conception rate at first service, interval between services in animals returning for insemination, the number of short cycles, length of first oestrous cycle and season of calving, and concluded that the low frequency of normal cycles is to a large extent due to heats which remained undetected by visual observation in Arsi cows under artificial insemination programmes.